Aerial Insect Biodiversity Responses to Prescribed Fire in an Eastern Grassland Habitat - Radin, Allison Qing (My University, 2025)
Grasslands in the Eastern United States are a biodiverse, but quickly vanishing, habitat type. Public land managers are beginning to incorporate prescribed fire into these fire-adapted systems to achieve cultural and natural resource conservation goals. While the effects of fire on plants are more widely documented, knowledge regarding the effects of fire on insect communities remains sparse. Following a prescribed burn in western Maryland, USA, no changes in community assemblage, species richness, or species diversity were found, but a significant decline in insect abundance was found. Insect species richness and abundance followed common growing season trends, peaking in mid-summer. Although these results follow general trends supported by global meta-analysis of insect community response to fire, the site and habitat specific responses of taxa make it difficult for public land managers to make species-specific management decisions without further detailed research.
Keywords: prescribed burn; insect biodiversity; aerial insects; Eastern grassland; Western Maryland; malaise trap; insect community composition